(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper has an objective to study the drama of His Majesty King Vajiravudh in the subject of MADANABADHA which publicly appeared in the Basic Education Core Curriculum and performance in schools. The scope of the study emphasized on teaching management, drama staging on the MADANABADHA and royal writings that appeared in the Basic Education Core Curriculum. The results show that the drama of MADANABADHA is a teaching and learning tool for teachers to disseminate information, knowledge, news, ideas, practices through demonstration, viewing of performances and practices for students to learn democracy, see rights and equality in finding woman’s partners to be assertive, good leadership and a good follower. It is to develop one’s own skill for both body and mind, intelligence, knowledge and morality with ethics and culture of living and to be able to live happily with others consistent with strategy of the National Education Management Plan and the development of learner’s quality to have competency and desirable characteristics. In addition, the royal writing “MADANABADHA” is regarded by the club literature as a well-written book proposed as the selective literature according to the announcement of Ministry of Education which contains contemporary contents. By using rose as a symbol that most people understand in the meaning of love, it represents the right and equality of women that is an important part of the development of Thailand towards becoming a concrete democracy. It plays an important role in the royal drama “MADANABADHA” in King Vajiravudh to be appeared in the basic education system and became popular in educational institutions from the past to present.